2018
DOI: 10.1029/2018jc014036
|View full text |Cite
|
Sign up to set email alerts
|

Projected Freshening of the Arctic Ocean in the 21st Century

Abstract: Using state‐of‐the‐art models from the Coupled Model Intercomparison Project phase 5 (CMIP5), this study found the upper Arctic Ocean likely to freshen considerably in the future. Arctic Ocean average sea surface salinity is projected to decrease by 1.5 ± 1.1 psu, and the liquid freshwater column is projected to increase by 5.4 ± 3.8 m by the end of the 21st century under the Representative Concentration Pathway 8.5 (RCP8.5) scenario. Most freshening would occur in the Arctic Ocean basins, that is, the Canada,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
82
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(94 citation statements)
references
References 50 publications
12
82
0
Order By: Relevance
“…The models show some common biases with respect to observations (e.g., the Polar Science Center Hydrographic Climatology, Steele et al 2001): the Beaufort gyre is more spatially diffuse, situated further from Canada and Alaska, and the central Arctic is overly fresh. These biases are also clear in the CMIP5 multi-model mean freshwater distribution (Shu et al 2018).…”
Section: A Representation Of Arctic Freshwatermentioning
confidence: 74%
See 2 more Smart Citations
“…The models show some common biases with respect to observations (e.g., the Polar Science Center Hydrographic Climatology, Steele et al 2001): the Beaufort gyre is more spatially diffuse, situated further from Canada and Alaska, and the central Arctic is overly fresh. These biases are also clear in the CMIP5 multi-model mean freshwater distribution (Shu et al 2018).…”
Section: A Representation Of Arctic Freshwatermentioning
confidence: 74%
“…Ding et al (2016) examined the processes governing the seasonal freshwater cycle in CMIP5 models, but otherwise the only intercomparison of Arctic Ocean freshwater and/or hydrography in models of the same generation of the CMIP5 models thus far comes from Arctic Ocean CORE-II studies, which considered forced (non-coupled) model simulations (Wang et al 2016;Ilicak et al 2016). Shu et al (2018) assess the projected changes of the CMIP5 multi-model mean freshwater content in the 21st century.…”
Section: A Representation Of Arctic Freshwatermentioning
confidence: 99%
See 1 more Smart Citation
“…Pacific water inflows Increased inflows are projected to at least mid-twenty-first century (e.g, Shu et al, 2018), here the monthly projections are based on the observed mean monthly increases in PW over the last 25 years (cf. Woodgate, 2018vs.…”
Section: Regionality and Seasonality Of Freshwater Sources Set The Gementioning
confidence: 99%
“…In the Iceland Sea, above 200 m, there is, in contrast to the other regions, a decrease in ALK in the RCP8.5 simulation, which has a negative impact on the pH. This is probably related to an increased export of freshwater from the Arctic Ocean (Shu et al, 2018).…”
Section: Drivers Of Ocean Acidificationmentioning
confidence: 85%